IOS 6 application development for dummies - Goldstein, Neal; Wilson, David A., 1943- (--For dummies., 2013)
Create incredible apps for the iPhone and iPad using the latest features of iOS 6 You could be the one who creates the next super app - one that is universal, works for both the iPhone and iPad, and is a top seller. It's a great goal, and the road starts here, with this energizing guide. Whether you're a budding programming hobbyist or a serious developer looking to hit it big, the information in this book is what you need. Learn how to join Apple's developer program, understand key differences between iPad and iPhone apps, download the latest SDK, create great user experiences, an.